A RIG-I-like receptor directs antiviral responses to a bunyavirus and is antagonized by virus-induced blockade of TRIM25-mediated ubiquitination - Min, Yuan-Qin; Ning, Yun-Jia; Wang, Hualin; Deng, Fei (The Journal of biological chemistry, 2020)
The RIG-I-like receptors (RLRs) retinoic acid-inducible gene I protein (RIG-I) and melanoma differentiation-associated protein 5 (MDA5) are cytosolic pattern recognition receptors that recognize specific viral RNA products and initiate antiviral innate immunity. Severe fever with thrombocytopenia syndrome virus (SFTSV) is a highly pathogenic member of the RIG-I, but not MDA5, has been suggested to sense some bunyavirus infections; however, the roles of RLRs in anti-SFTSV immune responses remain unclear. Here, we show that SFTSV infection induces an antiviral response accompanied by significant induction of antiviral and inflammatory cytokines and that RIG-I plays a main role in this induction by recognizing viral 5'-triphosphorylated RNAs and by signaling via the adaptor mitochondrial antiviral signaling protein. Moreover, MDA5 may also sense SFTSV infection and contribute to IFN induction, but to a lesser extent. We further demonstrate that the RLR-mediated anti-SFTSV signaling can be antagonized by SFTSV nonstructural protein (NSs) at the level of RIG-I activation. Protein interaction and MS-based analyses revealed that NSs interacts with the host protein tripartite motif-containing 25 (TRIM25), a critical RIG-I-activating ubiquitin E3 ligase, but not with RIG-I or Riplet, another E3 ligase required for RIG-I ubiquitination. NSs specifically trapped TRIM25 into viral inclusion bodies and inhibited TRIM25-mediated RIG-I-Lys-63-linked ubiquitination/activation, contributing to suppression of RLR-mediated antiviral signaling at its initial stage. These results provide insights into immune responses to SFTSV infection and clarify a mechanism of the viral immune evasion, which may help inform the development of antiviral therapeutics.